Studying Brains. What could neurometaphysics be to NeurotechEU? - Bransen, Jan; Oude Maatman, Freek (Frontiers in Neuroscience, 2023)
This paper explores the concept of neurometaphysics, its topics and its approach. It warns against an endemic Cartesianism that somehow seems to survive explicit refutations by implicitly persisting in our conceptual scheme. Two consequences of this persisting Cartesian legacy are discussed, the isolated brain assumption and the idea that activity requires identifiable neural ‘decisions’. Neuropragmatics is discussed as offering the promise of progress in neurometaphysics, by emphasizing that (1) studying brains interact organically with their environment, and (2) studying brains requires an attitude of continuous learning.